The Issue of Assessing the International Competitiveness of Commercial Banks and Their Improvements - Abdimuminov Bokhodir Alisher ugli (Zien Journals, 2022)
This article has developed strategies aimed at improving the effectiveness of competition in the banking system and the table is reflected in the criteria for competitiveness, as a result, commercial banks;the development of a competitive environment reflects the importance of the principles aimed at improving efficiency and competitiveness
Keywords: Competitive environment; bank competitiveness; evaluation of bank efficiency